World Views and the Problem of Synthesis
XXIII, 370 p.
Keywords: This book considers philosophy to be more than mere reflection. Through philosophy, humankind can give meaning to the world. In part, this book re-evaluates the philosophy of Leo Apostel, who dedicated his life to the investigation of the use of philosophy in everyday life. But it is also a presentation of international research carried out along the lines of the worldviews project. The contributions address not only professional philosophers, but also students, teachers, academics and everyone interested in the relationship between philosophy and the world.